2016
DOI: 10.1186/s13045-016-0236-7
|View full text |Cite
|
Sign up to set email alerts
|

CCR9 in cancer: oncogenic role and therapeutic targeting

Abstract: Cancer is currently one of the leading causes of death worldwide and is one of the most challenging major public health problems. The main challenges faced by clinicians in the management and treatment of cancer mainly arise from difficulties in early diagnosis and the emergence of tumor chemoresistance and metastasis. The structures of chemokine receptor 9 (CCR9) and its specific ligand chemokine ligand 25 (CCL25) have been elucidated, and, interestingly, a number of studies have demonstrated that CCR9 is a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 65 publications
0
54
0
Order By: Relevance
“…CCR9 expression is selectively increased on CD4 + T cells in T-ALL, inducing chemotactic migration by T-ALL CD4 + cells [20, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…CCR9 expression is selectively increased on CD4 + T cells in T-ALL, inducing chemotactic migration by T-ALL CD4 + cells [20, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…Chemokines/chemokine receptors take part in all stages of tumor development, including immune cells recruitment, neovascularization, tumor proliferation, invasion, and metastasis [26,27]. CCR9 interacts with its exclusive ligand CCL25 and results in trafficking of both lymphocytes and tumor cells to participate in tumor immunity and tumor development [11,16,17,[27][28][29][30]. More and more studies have indicated that CCR9 could be viewed as an oncogenic biomarker in predicting metastasis and prognosis for cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Increased CCR9 expression was correlated with poor overall survival [9,14]. CCR9/CCL25 axis played an important role in tumor invasion, migration, drug resistance and apoptosis [15,16]. The application of anti-CCR9 antibody could inhibit the migration and invasion of tumor cells [17].…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that piscine CCR9 were predominantly expressed in hematopoietic and/or immune-related tissues, such as the blood, head kidney, kidney, and gill. In mammals, CCR9 was mainly distributed in immature T lymphocytes and on the surface of intestinal cells (Tu et al 2016). Recent studies have provided Figure 4.…”
Section: Tissue Distribution Of the Rcccr9mentioning
confidence: 99%